Structural Covariance Network Disruption and Functional Compensation in Parkinson’s Disease - Zhou, Cheng; Gao, Ting; Guo, Tao; Wu, Jingjing; Guan, Xiaojun; Zhou, Weiwen; Huang, Peiyu; Xuan, Min; Gu, Quanquan; Xu, Xiaojun; Xia, Shunren; Kong, Dexing; et al. (Frontiers in Aging Neuroscience, 2020)
Purpose: To investigate the structural covariance network disruption in Parkinson’s disease (PD), and explore the functional alterations of disrupted structural covariance network. Methods: A cohort of 100 PD patients and 70 healthy participants underwent structural and functional magnetic resonance scanning. Independent component analysis (ICA) was applied separately to both deformation-based morphometry maps and functional maps with the same calculating parameters (both decomposed into 20 ICs and computed 20 times Infomax algorithm in ICASSO). Disrupted structural covariance network in PD patients was identified, and then, we performed goodness of fit analysis to obtain the functional network that showed highest spatial overlap with it. We investigated the relationship between structural covariance network and functional network alterations. Finally, to further understand the structural and functional alterations over time, we performed a longitudinal subgroup analysis (51 patients were followed up for two years) with the same procedures. Results: In cross-sectional analysis, PD patients showed decreased structural covariance between anterior and posterior cingulate subnetworks. The functional components showed best overlap with anterior and posterior cingulate structural subnetworks were selected as anterior and posterior cingulate functional subnetworks. The functional connectivity between them was significantly increased (assessed by Functional Network Connectivity toolbox). And the increased functional connectivity was negatively correlated with cingulate structural covariance network integrity. Longitudinal subgroup analysis showed cingulate structural covariance network disruption was worser at follow-up, while the functional connectivity between anterior and posterior cingulate network was increased at baseline and decreased at follow. Conclusion: This study indicated that cingulate structural covariance network displayed a high susceptibility in PD patients. This study indicated that cingulate structural covariance network displayed a high susceptibility in PD patients. Considering that disrupted structural covariance network coexisted with enhanced/remained functional activity during disease development, enhanced functional activity underlying the disrupted cingulate structural covariance network might represents a temporal compensation for maintaining clinical performance.